Maternal Considerations to Termination of Down Syndrome Pregnancies [10L]. (May 2018) - Fanucchi, Hannah; Cui, Yiwen; Phillips, Carolyn; Rijhsinghani, Asha
Abstract : INTRODUCTION: To assess maternal factors that influence a patient's decision to terminate a pregnancy affected by Down syndrome. METHODS: This retrospective study included all patients diagnosed with fetal Down syndrome via amniocentesis between 1990 and 2006 at the University of Iowa Hospital and Clinics. Patients were stratified into two groups by maternal age and socio-clinical data were collected from initiation of prenatal care to the end of the pregnancy. RESULTS: Total of 261 patients were diagnosed with Down syndrome fetuses, 106 (40.6%) of which belonged to women <35 years old and 155 (59.4%) to >35 year old. Fifty pregnancies (47.2%) in the former group were terminated while 107 (69.0%) were terminated for the latter. Patients >35 yo were diagnosed at a significantly earlier gestational age compared to those <35 yo (16.8+1.9 versus 18.9+2.9, P <.03). Older patients also had a longer time period from diagnosis to termination than younger patients (2.5 versus 2.0 weeks). CONCLUSION: Few studies have focused on the patient who must make the ultimate decision on her pregnancy in face of a positive amniocentesis for Down syndrome. We found that the key difference between older women who chose termination compared to those <35 yo is an earlier gestational age at amniocentesis, with a longer period available for decision making. This stresses the importance of availability of screening programs for early karyotyping and diagnosis of Down syndrome and early education.